2022
DOI: 10.1515/hsz-2022-0156
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-6838-5p suppresses the self-renewal and metastasis of human liver cancer stem cells through downregulating CBX4 expression and inactivating ERK signaling

Abstract: Hepatocellular carcinoma (HCC) is the most common primary human liver malignancy with high mortality. Liver cancer stem cells (CSCs) have been demonstrated to contribute to the recurrence, metastasis and drug resistance of liver cancer. Human HCC cohort analysis indicated that the epigenetic regulator polycomb chromobox homologue 4 (CBX4) was overexpressed in human HCC. Moreover, we found that CBX4 expression was significantly higher in CD44+ CD133+ Hep3B CSCs. Functionally, we demonstrated that CBX4 regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…MiR-6838-5p was down-regulated in a variety of cancer types, including breast cancer [ 20 ], stomach cancer [ 21 ] and Osteosarcoma [ 22 ], as demonstrated in the prior work. It has been discovered that miR-6838-5p inhibits the self-renewal and metastasis of human HCC stem cells via deactivating ERK signaling and downregulating CBX4 expression [ 23 ]. In line with other studies, we discovered miR-6838-5p repressed the expression of PTPN4 and reduced HCC growth, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-6838-5p was down-regulated in a variety of cancer types, including breast cancer [ 20 ], stomach cancer [ 21 ] and Osteosarcoma [ 22 ], as demonstrated in the prior work. It has been discovered that miR-6838-5p inhibits the self-renewal and metastasis of human HCC stem cells via deactivating ERK signaling and downregulating CBX4 expression [ 23 ]. In line with other studies, we discovered miR-6838-5p repressed the expression of PTPN4 and reduced HCC growth, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA RNA associated with metastasis-11 (RAMS11) promotes the growth and metastasis of PCa cells by binding CBX4 and activating the expression of topoisomerase IIα (TOP2α) (162). miR-129-5p (163) and miR-515-5p (164) in BC, miR-507 in GC (165), miR-6838-5p in HCC (166) and miR-497-5p in CCA (167) target CBX4 to regulate the biological characteristics of human cancers. BMP2 increases miR-181b levels to directly target and inhibit CBX4 expression in adamantinomatous craniopharyngioma (ACP), resulting in reduced regulation of CBX4-dependent HDAC3 nuclear translocation, RUNX2 activation/osteoblast differentiation and calcium deposition in ACP (168).…”
Section: Cbxs Regulate Biological Tumor Processes Through Epigenetic ...mentioning
confidence: 99%
“…Si et al [ 61 ] found that miR-219 regulates the expansion of LCSCs through the E-cadherin pathway. Dou et al [ 62 ] showed that miR-6838-5p inhibited self-renewal and metastasis of LCSCs by down-regulating CBX4 expression and inhibiting ERK signaling. In addition, miR-589-5p inhibited MAP3K8 in HCC and inhibited CD90 CSCs[ 63 ].…”
Section: Roles Of Cscs In Lcmentioning
confidence: 99%